2008
DOI: 10.1055/s-2008-1073126
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile and Nitric Oxide Synthase Expression of Skeletal Muscle Fibers are Altered in Patients with Type 1 Diabetes

Abstract: We investigate muscle fiber composition, fiber-specific glycolytic and oxidative enzyme capacity and nitric oxide synthase (NOS) expression in skeletal muscle of patients with type 1 diabetes (T1D) compared to individuals with normal glucose tolerance (NGT). Vastus lateralis muscle was obtained by percutaneous biopsy from 7 T1D patients and 10 healthy controls with similar characteristics. Using cytophotometry, muscle fiber composition and fiber type-specific glycolytic and oxidative enzyme activities were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 23 publications
(45 reference statements)
4
27
0
1
Order By: Relevance
“…Consistent with studies using STZ rodents that report reductions in oxidative capacity [62], [64], [65], we also found reductions in SDH and COX activity in the GP muscles in the 8 week Px group. Despite these reductions in oxidative enzymes, we observed attenuation in relative muscular fatigue rates at both 4 and 8 weeks after Px- compared to Sham- surgery (Figure 2 inset).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with studies using STZ rodents that report reductions in oxidative capacity [62], [64], [65], we also found reductions in SDH and COX activity in the GP muscles in the 8 week Px group. Despite these reductions in oxidative enzymes, we observed attenuation in relative muscular fatigue rates at both 4 and 8 weeks after Px- compared to Sham- surgery (Figure 2 inset).…”
Section: Discussionsupporting
confidence: 91%
“…type IIb/d fibers), which is indeed counter to what we have speculated to have occurred in these animals. It may be that the small reduction in peak twitch amplitude at 8 weeks might explain the reduced contraction and relaxation time in these animals, although an increase in the number of type II fibers (although with reduced fiber areas) with T1DM, as has been observed in human studies of T1DM [62], [63], can not be ruled out.…”
Section: Discussionmentioning
confidence: 89%
“…Muscle growth and development is significantly impaired in T1DM, resulting in reduced muscle mass and myofiber size, poor metabolic control, and a switch to a glycolytic phenotype (Andersen et al, 1997, 2004; Crowther et al, 2003; Fritzsche et al, 2008; Krause et al, 2009, 2013). While initial studies in human T1DM reported no difference in capillary density (Leinonen et al, 1982), investigations in T1DM mice illustrate that the disease is associated with a decline in skeletal muscle capillarization and angiogenesis (Kivelä et al, 2006; Krause et al, 2009).…”
Section: Skeletal Muscle In Diabetes Mellitusmentioning
confidence: 99%
“…Some authors report decreased peak oxygen uptake and/or reduced submaximal cardiac output (15,24,27), yet, other investigators showed that peak oxygen uptake is not affected in patients with type 1 diabetes (13,17,37). However, none of these authors have concurrently investigated both skeletal muscle structure and in vivo (mitochondrial) function and combined these data with the functional assessment of peak oxygen uptake and peak cardiac output.…”
mentioning
confidence: 99%